The Relationship between Mentoring Program and Mentees Psychological and Emotional Support: Personality as a Moderator - Rizal, Abu Bakar; Hii, Kong Loi (Faculty of Cognitive Sciences & Human Development UNIMAS, 2016)
This study aims to examine the relationship between mentoring program, personality and mentee outcomes. One hundred respondents from different faculties in one of the universities in East Malaysia were involved in this study. Pearson Correlation was employed to determine the relationship between mentoring program and mentee outcomes, personality and mentee outcomes, mentoring program and psychological and emotional support. The results showed that there was a significant relationship between mentoring program and mentee outcomes. Multiple Regressions was used to assess whether personality act as a moderator between mentoring program and mentee outcomes. The findings indicated that personality moderates the relationship between mentoring program and mentee outcomes. The findings of this research are beneficial for mentoring program in universities in Malaysia, especially, in ensuring better mentoring outcomes. Implication of this research on organization and individuals was also discussed.